Factors Affecting Passenger Satisfaction of Low-Cost Airlines - แช่มบำรุง, พัชรพร; แก้วรัตน์, ณัฏฐณิชา; ก๊กรัมย์, อินทิรา; เทพแก้ว, ฟานิสต้า (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research entitled "Factors Influencing Passenger Satisfaction with Low-Cost Carriers" aims: 1) to study the levels of passenger opinions toward service quality factors, and 2) to analyze the influence of service quality factors on passenger satisfaction. This study employed a mixed-methods research design. For the quantitative phase, data were collected via questionnaires from 400 passengers in Thailand using Convenience Sampling. Statistical analyses included percentage, mean, standard deviation, and Multiple Regression Analysis. For the qualitative phase, a Focus Group Interview was conducted with 10 frequent passengers to further elaborate on the quantitative findings.           The research findings revealed that:• Quantitative Results: The overall level of passenger opinions toward service quality factors was at a high level. Multiple Regression Analysis indicated that Convenience was the most significant factor influencing satisfaction at a 0.05 significance level, followed by Safety, Staff Service, Price and Value, and Punctuality, respectively.• Qualitative Results: The interviews provided deeper insights, showing that the most critical aspects of convenience were the speed of the check-in process and the user-friendliness of the airline’s mobile application, both of which significantly drive overall passenger satisfaction.           These findings suggest that low-cost carriers should prioritize enhancing self-service technologies to improve convenience, ultimately fostering passenger satisfaction and loyalty.